The effectiveness of cognitive rehabilitation on memory disorders in the first stages of Alzheimer’s disease - Τσάνταλη Ελένη; Τσολάκη Μάγδα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF